Shexiang Baoxin Pill, a Proprietary Multi-Constituent Chinese Medicine, Prevents Locomotor and Cognitive Impairment Caused by Brain Ischemia and Reperfusion Injury in Rats: A Potential Therapy for Neuropsychiatric Sequelae of Stroke - Qin, Zong-Shi; Zheng, Yu; Zhou, Xi-Dan; Shi, Dong-Dong; Cheng, Dan; Shek, Chun Shum; Zhan, Chang-Sen; Zhang, Zhang-Jin (Frontiers in Pharmacology, 2021)
Ischemic stroke is the most common type of cerebrovascular event and also the leading cause of disability, and post-stroke cognitive impairment occurs frequently in stroke survivors. Shexiang Baoxin Pill (SBP) is a proprietary Chinese medicine, initially used to treat cardiovascular diseases. Herein, we aim to explore the effects of SBP on oxygen glucose deprivation and reoxygenation (OGD/R) in neuronal cells (CATH.a) and cerebral ischemia/reperfusion injury induced post-stroke cognitive impairment in middle cerebral artery occlusion (MCAO) rat model. MCAO rats received two doses of oral SBP treatment (28 mg/kg or 56 mg/kg) after 1 h of operation and once daily for 2 weeks continuously. Behavioral tests, immunoblotting, and immunofluorescence were examined after 14 days. Current data suggest that SBP enhanced cell viability and downregulated apoptosis via activating the PI3K/Akt signaling pathway in CATH.a cells. Furthermore, 14 days of SBP treatment promoted the recovery of learning and locomotor function in the MCAO rats. SBP activates the PI3K/Akt signaling pathway, up-regulated the expression of p-Akt, p-GSK3β, as well as the expression of NMDAR1, PSD-95, and AMPAR. Also, SBP down-regulated the expression of p-CaMKII. These results indicated that long-term SBP treatment might be a potential option for cognitive impairment induced by the ischemic stroke.